Bakers and Basques : a social history of bread in Mexico - Weis, Robert, 1971- (University of New Mexico Press, 2012)
More than a book about bread, Bakers and Basques places food and labor at the center of the upheavals in Mexican history from independence to the aftermath of the Mexican Revolution.